Analisis Pengaruh Strategi Pembelajaran Heuristik Terhadap Kemampuan Berpikir Kreatif Siswa SMP - ., Kewia Primandani; ., Muhammad Irfan Rumasoreng (Jurnal Pendidikan, Sains Dan Teknologi, 2023)
One of the skills that students need to have in the 21st century is the ability to think creatively. In carrying out learning activities in the classroom, teachers must balance students' strong creative thinking skills with the learning methodology they use. This study looks at how heuristic learning techniques affect students' capacity to think original. Experimental research is the term for this type of research. Grade VIII students of SMP Negeri 2 Godean were used as research subjects. Interviews, observations, and tests were used in the data collection process. According to the study findings, the percentage of creative students scored 8.38% before treatment and jumped to 62.50% afterward. Before receiving treatment, students generally got an average score of 38.75, then rose to 84.22 after receiving treatment. In accordance with the analysis of the data presented above, it can be concluded that heuristic learning strategies affect the creative thinking abilities of junior high school students.